Molecular characteristics of the edge cells responsible for expansion of the chick embryo on the vitelline membrane. Issue 9 (21st September 2022) - Lee, Hyung Chul; Fadaili, Yara; Stern, Claudio D.
Abstract : Abstract : During early avian development, only a narrow band of cells (the edge cells, also called 'margin of overgrowth') at the rim of the embryo is responsible for blastoderm expansion by crawling over the vitelline membrane (VM) to cover the whole egg yolk in just 4 days (a process called epiboly). Surprisingly, this has not yet been studied in detail. Here we explore the edge cells of the chick embryo using in situ hybridization, immunohistochemistry and live imaging. Morphological and molecular properties reveal that the edge has a distinctive structure, being subdivided into sub-regions, including at least four distinct zones (which we name as leading, trailing, deep and stalk zones). This allows us to study reorganization of the edge region that accompanies reattachment of an explanted blastoderm to the VM. Immunohistochemistry uncovers distinct polarized cellular features resembling the process of collective cell migration described in other systems. Live imaging reveals dynamic lamellipodial and filopodial activity at the leading edge of the outermost cells. Our data provide evidence that edge cells are a distinct tissue. We propose that edge cells may be a useful model system for the study of wound healing and other closure events in epithelial cell sheets.